Integrated Radiation Diagnostics of Pulmonary Complications of Pneumonia in Children - Gulnora Akmalovna, Yusupaliyeva; Elyor Allayarovich, Akhmedov; Laylo Rustamjanovna, Sultanova; Temur Abdurashidovich, Yuldashev; Shakhnoza Ortikboy Kizi, Ortikboeva (International Journal of Psychosocial Rehabilitation, 2020)
An important role in the diagnosis of pneumonia and its complications is given to the integrated use of radiation research techniques. The possibilities of using new methods of radiation diagnostics (digital radiography, ultrasound, multispiral computed tomography, and magnetic resonance imaging) have increased. Each method has characteristic diagnostic capabilities and indications for its use. The possibility of early and differential diagnosis of pneumonia complications using the above types of studies is of great importance for the timely conduct of adequate therapy, which prevents the progression and development of complications of the disease. The cited semiotics of complicated pneumonia using new types of imaging in radiation diagnostics is presented incompletely. Currently, in the early and differential diagnosis of pneumonia complications, there is no experience with complex radiation diagnostic methods of examination; the algorithm for their application has not been clarified. In a few works, there is only data on their capabilities in the diagnosis of pneumonia complications, but there is no information on the integrated use with effectiveness. In modern medicine, the study of pathological processes, the assessment of the morphological and functional state of tissues and organs, the diagnosis and differential diagnosis, and treatment control are unthinkable without X-ray, ultrasound, and magnetic resonance imaging studies. These studies are accessible, informative, and, importantly, non-traumatic.